Análisis financiero de la Cooperativa de Ahorro y Crédito Jardín Azuayo, Agencia Saraguro, periodo 2020 – 2021 - Armijos Segarra, Jessica Marilu (2023)
Savings and Credit Cooperatives have a cardinal role in the economy of the countries, since they promote favorable environments for the dynamization of the market by granting loans to individuals and micro-entrepreneurs. To this effect, the general objective of this study was: To analyze financially the Savings and Credit Cooperative "Jardin Azuayo" of the Saraguro Agency, period 2020 - 2021, with a basis for an adequate management. The methodology used is based on the use of methods of vertical and horizontal analysis and financial indicators complemented with an interview to the manager of the Agency, in order to verify the real financial situation of the Savings and Credit Cooperative, and to be able to take the necessary corrective measures for the proper functioning of the same, obtaining as results that the financial institution, maintains most of its assets in credit portfolio, which has a low level of delinquency of 0.67% for the year 2021, a profitability of 3.11%, non-performing assets of 3.92%; However, it obtained a low liquidity of 6.36%, and presents a minimum growth of its members. In conclusion, the cooperative is in a favorable financial and economic situation.